Perbandingan Efektivitas Senam Etnis Batak Toba Dan Senam Tai Chi Terhadap Penurunan Kadar Gula Darah Pada Penderita Dm Tipe 2 Di Puskesmas Kabanjahe - Valentina Yovita Br Sitorus; Zesika Putri Br Simbolon (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: The increasing prevalence of Type 2 Diabetes Mellitus (DM) imposes significant health and economicburdens, necessitating effective, low-cost, and culturally acceptable non-pharmacological management approaches. Objective: To compare the effectiveness of Batak Toba Ethnic Gymnastics and Tai Chi Gymnastics in reducing fasting blood glucose levels among Type 2 DM patients at Kabanjahe Public Health Center. Methods: A quantitative study with quasi-experimental Two Group Pretest-Posttest Design was conducted. The sample consisted of 24 female Type 2 DM patients meeting inclusion criteria, divided equally into two intervention groups (12 respondents each). The intervention was performed for two weeks, three sessions per week (6 total sessions). Data were analyzed using Paired Sample T-Test and Independent Sample T-Test. Results: The Batak Toba Ethnic Gymnastics group experienced a mean reduction in fasting blood glucose of 37.92 mg/dL (from 179.92 mg/dL to 142.00 mg/dL; p = 0.000). The Tai Chi Gymnastics group showed a smaller reduction of 4.25 mg/dL (from 183.92 mg/dL to 179.67 mg/dL; p = 0.005). The Independent Sample T-Test confirmed a significant difference in effectiveness between the two groups (p = 0.000). Conclusion: Batak Toba Ethnic Gymnastics is proven to be far more effective in reducing fasting blood glucose levels compared to Tai Chi Gymnastics among Type 2 DM patients at Kabanjahe Public Health Center, likely due to its more dynamic, active movements and its cultural alignment with the local community.